A non-linear analysis of the impacts of natural resources and education on environmental quality: Green energy and its role in the future. (December 2022) - Liu, Haiying; Alharthi, Majed; Atil, Ahmed; Zafar, Muhammad Wasif; Khan, Irfan
Abstract: Human accomplishments have increased the complexity and interconnectedness of environmental threats, resulting in widespread effects on people, ecosystems, and economies worldwide. In addition to overpopulation, pollution, burning fossil fuels, and deforestation, humans also impact the physical environment in many ways. These changes have contributed to climate change, soil erosion, poor air quality, and undrinkable water. We investigate the linear and non-linear effects of natural resources and education on CO2 emissions in the Latin American (LA) group of nations considering the roles of green energy, foreign remittances, and economic growth from 1990 to 2020. We have developed a comprehensive empirical analysis that applied second-generation advanced econometric methodologies in this study. The results of this research disclosed that natural resources pose a non-linear impact on environmental quality. The low level of natural resources benefits the environment in the LA panel, but higher use of natural resources ultimately intensifies CO2 emissions. Hence, a U-shaped association between natural resources and CO2 emissions is found in the LA panel. In the linear model, natural resources also boost CO2 emissions. Alongside this, education also intensifies CO2 emissions in the selected sample. Green energy and remittances mitigate CO2 emissions and thereby improve environmental quality. Graphical abstract: Image 1 Highlights: Environmental impact of linear and non-linear natural resources checked. Economic growth escalates environmental deterioration. The environment can improve after a threshold level of economic growth. Extraction of natural resources poses detrimental effects on the environmental quality. A U-shaped association between natural resources and CO2 emissions is found.